A Study on Purchase behavior of rural and urban consumers about Organic food in selected areas of Andhra Pradesh - Ashok Chowdary. K; Prof. M. V. Ram Prasad; Dr. S. Chand Basha, (International Journal of Management Studies (IJMS), 2021)
Organic food category in the retailing industry is gaining importance and increasing its shelf space in different retail formats in domestic market and in the international market. Organic food market size is about Rs. 1000 crore as per the private sources and it is growing at the growth rate of 25 to 30 % constantly since last 5 to 6 years. Out of the total market 70 % is coming from export market and 30% is from Domestic market. Around 5Mn hectares is the area being used for cultivation of organic food in India and is still increasing day by day due to high prices being paid to the farmers. It is expected to grow at around 30 to 35% CAGR in the next 5 to 6 years. It is observed that sustainability of organic food is increasing with the increasing farmers’ interest in organic farming. However it is observed that the manufacturers are facing problems because of the costs involved in the supply chain. In this article we have tried to focus on the perception of different consumers about the factors like price, availability, branding etc that influence the purchase of Organic food. Also we have tried to find out the difference in perception of consumers about the organic food in rural and urban areas.